IMPACT OF SOIL STERILIZATION FROM DIFFERENT LOCATIONS, WHEAT SEEDS CLEANING AND THEIR INTERACTIONS ON WEED CONTROL, AND YIELD AND YIELD COMPONENTS - Horamani, K. F.M.,; Sarmamy, A.O.I., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
REFERENCES • Ahmad, S., M., Raza, M., Saleem, M., Zaheer, R., Iqbal, I. Haider, M. Aslam, M. Ali, and I. Khan, 2020.'Significance of partial root zone drying and mulches for water saving and weed suppression in wheat', J. Anim. Plant. Sci, 30, 154-162.• Al-Chalabi, F. 2003. 'Biological response to wheat as control of the weeds diclofop-mathy herbicide alternating with the herbicide 2.4-D and the effect in the bio', Iraqi Agric. Sci., 24(1), 84-110• Al-Chalabi, F. T. and H. S. M. Al-Agidi, 2010. 'weed compettetion effect on wheat cultivares and its impact on growth characterstics ', Anbar journal od agricultural sciences 8(4), : 12• Ali, K. A., M. H. Qadir, S. O. Rasoul, and S. S. Ali, 2016. 'physiological and yield responses of wheat (Triticum aestivum) to different herbicide treatments', JZS (2016) 18-04 (Part-A).• Amare, T., Sharma, J. and K. Zewdie, 2014. 'Effect of weed control methods on weeds and wheat (Triticum aestivum L.) yield', World journal of agricultural research, 1(2), : 124-128• Ashrafi, Z. Y., Mashhadi, H. R., Sadeghi, S. and Blackshaw, R. E. (2009) 'Study effects of planting methods and tank mixed herbiciedes on weeds controlling and wheat yield', Journal of Agricultural Science, 1(1), : 101• Ayana, B. 2019. Effects of Seed Rates and Herbicides Application on Weed Management and Productivity of Wheat (Triticum Aestivum L.) at Holeta Ethiopia. Jimma University• Baktash; F. Y. and M. A. Naes. 2016. Evaluation bread wheat pure lines under effect of unlike seeding rates for grain yield and it,s component. Iraqi Journal of Agricultural Sciences, 47(5):1132-1140. https://doi.org/10.36103/ijas.v47i5.488• Baktash; F. Y. and M. A. Naes. 2016. Evaluation bread wheat pure lines under effect of unlike seeding rates. Iraqi Journal of Agricultural Sciences, 47(5):1141-1150. https://doi.org/10.36103/ijas.v47i5.489• Benvenuti, S., Macchia, M. and Miele, S. (2001) 'Quantitative analysis of emergence of seedlings from buried weed seeds with increasing soil depth', Weed Science, 49(4). 528-535• Black, C., D. Evans, and R. Dinauer, 1965. 'Methods of soil analysis, Madison, WI: American Society of Agronomy. Vol. 9, : 653-708• Burkov, A., A. Glushkov, and V. Lazykin, 2018. 'Development of grain-cleaning machines working on fractional technology', Perm Agrarian Journal, 23(3), : 12-19• Castillo-Luna, M. d. P. and R. Gómez-Gómez, 2016. 'Effect of soil steam sterilization on weed seeds', Agronomía Mesoamericana, 27(2), : 409-413• Chaudhary, S. U., M. Hussain, M. A. Ali, and J. Iqbal, 2008. 'Effect of weed competition period on yield and yield components of wheat', J. Agric. Res, 46(1), : 47-54• Chicouene, D. 2020. 'Inventory and mechanisms of cultural control practices for weed management, a review', Journal of Research in Weed Science, 3(4), : 490-528• Dhahi A.M. and F. Y. Baktash. 2018. Evaluation performance of bread wheat pure lines to growth traits and proline. Iraqi Journal of Agricultural Sciences, 49(1):1-10. https://doi.org/10.36103/ijas.v49i1.198• Dhahi A.M. and F. Y. Baktash. 2018. Impact of moisture depletion percentages on some growth characters and yield for selected genotypes of bread wheat. Iraqi Journal of Agricultural Sciences, 49(2):160-170. https://doi.org/10.36103/ijas.v49i2.160• De Lucas Bueno, C. and R. Froud Williams, 1996. 'Effect of the seed size on the competitive ability of winter wheat cultivars', Annales ANPP (France).• Dietrich, P., S., Cesarz, N. Eisenhauer, and C. Roscher, 2020. 'Effects of steam sterilization on soil abiotic and biotic properties', Soil Organisms, 92(2), pp. 99–108-99–108• Edwards, J. T. and E. G. Krenzer Jr, 2006. 'Quality of Farmer‐Saved Wheat Seed is Variable in the Southern Great Plains', Crop Management, 5(1), : 1-7• Gharde, Y., Singh, P., Dubey, R. and Gupta, P. (2018) 'assessment of yield and economic losses in agriculture due to weeds in India', crop protection, 107, : 12-18• Hossain, M. 2015. 'recent perspective of herbicide: review of demand and adoption in world agriculture', Journal of the Bangladesh agricultural university, 13(452-2016-35850), : 13-24• Hussain, M. I., Abideen, Z., Danish, S., Asghar, M. A. and Iqbal, K. 2021.'Integrated Weed Management for Sustainable Agriculture', Sustainable Agriculture Reviews 52: Springer, : 367-393• ISWS, G. J. I. C. 2018. 'Fifty Years of Weed Research in India '. ISWS Golden Jubilee ,Internationasl Conference / Fifty years of weed reasearch in India, Jabalpur India, 2018: Indian Society of Weed Science (ISWS)/ ICAR-Directorate of Weed Research (DWR) Maharajpur.Jabalpur- 482 004 India ;Http://WWW.isws.org.in, 357p• Javaid, A., R. Bajwa, and T. Anjum, 2008. 'Effect of heat-sterilization and EM (effective microorganisms) application on wheat (Triticum aestivum L.) grown in organic-amended sandy loam soil', cereal research communications, 36(3), : 489-499• Kandasamy, S., N. Weerasuriya, D. Gritsiouk, G. Patterson, S. Saldias, S. Ali, and G. Lazarovits, 2020. 'Size variability in seed lot impact seed nutritional balance, seedling vigor, microbial composition and plant performance of common corn hybrids', Agronomy, 10(2), : 157• Khan, M. B., Asif, M., Hussain, N. and M. Iqbal, 2000. 'Agro-Economic impact of different weed control strategies in wheat', J. Res. Sci, 11(1), : 46-49• Khazaei, F., M., AghaAlikhani, S. Mobasser, , A., Mokhtassi-Bidgoli, H. Asharin, and H. Sadeghi, 2016. 'Evaluation of Wheat (Triticum aestivum, L.) seed quality of certified seed and farm-saved seed in three provinces of Iran', plant breeding and seed science, 73, : 99-115• Kiss, R., O.,Valkó, B. Tóthmérész, and P. Török, 2016. 'Seed bank research in Central-European grasslands-An overview'• Lollato, R. 2016. 'Wheat growth and development', Kansas State University Extension• Lollato, R., Mark, K., Jaenisch, B. and Haag, L. 2020. 'Wheat Grain Yield Response to Seed Cleaning and Seed Treatment as Affected by Seeding Rate During the 2018–2019 Growing Season in Kansas', Kansas Agricultural Experiment Station Research Reports, 6(5), : 24• Lynch, J. P. 2011. 'Root phenes for enhanced soil exploration and phosphorus acquisition: tools for future crops', Plant physiology, 156(3), : 1041-1049• Michael, P. J., Owen, M. J. and Powles, S. B. 2010. 'Herbicide-resistant weed seeds contaminate grain sown in the western Australian grainbelt', weed science, 58(4), : 466-472• Monaco, T. J., Weller, S. C. and Ashton, F. M. 2002. weed science: principles and practices. John Wiley & Sons, p. 388• Nishimura, A., Asai, M., Shibuya, T., Kurokawa, S. and Nakamura, H. 2015. 'A steaming method for killing weed seeds produced in the current year under untilled conditions', Crop Protection, 71, : 125-131• Norsworthy, J. K., Ward, S. M., Shaw, D. R., Llewellyn, R. S., Nichols, R. L., Webster, T. M., Bradley, K. W., Frisvold, G., Powles, S. B. and Burgos, N. R. 2012. 'Reducing the risks of herbicide resistance: best management practices and recommendations', Weed science, 60(SP1), : 31-62• Oerke, E. 2006. 'Crop losses to pests', The Journal of Agricultural Science, 144, : 31• Owen, M. J. and S. B. Powles, 2020. 'Lessons learnt: crop-seed cleaning reduces weed-seed contamination in Western Australian grain samples', Crop and Pasture Science, 71(7): 660-667• Pinto, J. G. C. P., Munaro, L. B., Jaenisch, B. R., Nagaoka, A. K. and Lollato, R. P. 2019. 'wheat variety response to seed cleaning and treatment after fusarium head blight infection', agrosystems, geosciences & environment, 2(1), : 1-8• Rasul, G. A. M. 2016. 'Effect of phosphorus fertilizer application on some yield components of wheat and phosphorus use efficiency in calcareous soil', journal of dynamics in agricultural research, 3(4): 46-51• Rehim, A., Farooq, M., Ahmad, F. and Hussain, M. 2012. 'Band placement of phosphorus improves the phosphorus use efficiency and wheat productivity under different irrigation regimes', international journal of agriculture and biology, 14(5).• Richardson, A. E., J. P., Lynch, P. R. Ryan, , Delhaize, E., Smith, F. A., Smith, S. E., P. R., Harvey, M. H.Ryan, , E. J. Veneklaas, and H. Lambers, 2011. 'Plant and microbial strategies to improve the phosphorus efficiency of agriculture', plant and soil, 349(1) : 121-156• Roberts, H. 1981. 'Seed banks in soils', Advances in applied biology, 6, : 1-55• Shen, J., Yuan, L., Zhang, J., Li, H., Bai, Z., Chen, X., Zhang, W. and Zhang, F. 2011. 'Phosphorus dynamics: from soil to plant', Plant Physiology, 156(3): 997-1005• Tawaha, A., M.Turk, and G. Maghaireh, 2002. 'Response of barley to herbicide versus mechanical weed control under semi‐arid conditions', Journal of Agronomy and Crop Science, 188(2), : 106-112• Tessema, T., D. Tanner, and M. Hasenna, (1996) 'Grass weed competition with bread wheat in Ethiopia. 2: Prediction of grain yield loss and implications for economic weed control'• Thomas, G. W. 1996. 'Soil pH and soil acidity', Methods of soil analysis. Part, 3(875), : 475-490• Thompson, K. and J. P. Grime, 1979.'Seasonal variation in the seed banks of herbaceous species in ten contrasting habitats', The Journal of Ecology, : 893-921• Tibola, C. S., J. M. C. Fernandes, and E. M. Guarienti, 2016. 'Effect of cleaning, sorting and milling processes in wheat mycotoxin content', Food Control, 60, : 174-179• Walker, R. H. 1995. 'Preventive weed management', Handbook of weed management systems, : 35-50